MANAGEMENT OF GRIDHRASI W.S.R TO ACUTE SCIATICA THROUGH PANCHAKARMA TREATMENT - *Kavita; Bhatted, Santosh Kumar (International Journal of Ayurveda and Pharma Research, 2019)
Gridhrasi or sciatica in modern language is one the common condition of loco motor system disorder; it is a pain dominant disease and reduces human activity. In Ayurveda texts it comes under Vatavyadhi. Aim: To successfully manage acute case of sciatica through Panchakarma treatment. Materials and Methods- An acute case of sciatica was taken under consideration and was given Panchakarma therapies like Kati Basti, Abhyanga, Matra Basti for 23 days. Results and conclusion: The patient got 83.3% improvement in SLR test and nerve discomfort. It was noted that Panchakarma therapy is highly effective in treating acute cases of sciatica.